2022
DOI: 10.1371/journal.pone.0273547
|View full text |Cite
|
Sign up to set email alerts
|

Combining ablative radiotherapy and anti CD47 monoclonal antibody improves infiltration of immune cells in tumor microenvironments

Abstract: Radiotherapy as an anti-tumor treatment can stimulate the immune system. However, irradiated tumor cells express CD47 to escape the anti-tumor immune response. Anti- CD47 Immunotherapy is a possible way to tackle this problem. This study evaluated the effect of single high dose radiotherapy combined with an anti-CD47 monoclonal antibody (αCD47 mAb) in CT26 tumor‐bearing BALB/c mice. We assessed the tumors volume and survival in mice 60 days after tumor implantation. Also, immune cell changes were analyzed by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Our observations regarding dose-dependent response of PD-L1 and CD47 to radiation in glioma models are consistent with previous studies in various cancer types. 38 , 39 , 40 Notably, expression of CD47 appears to be influenced by radiation in a context-dependent manner, either increasing 41 , 42 , 43 or decreasing, 44 depending on the cell/tissue type and radiation regimen. Increased CD206-expressing myeloid cells in more aggressive recurrent GBM samples compared to newly diagnosed cases supports previous findings, indicating the role of myeloid cells in GBM tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations regarding dose-dependent response of PD-L1 and CD47 to radiation in glioma models are consistent with previous studies in various cancer types. 38 , 39 , 40 Notably, expression of CD47 appears to be influenced by radiation in a context-dependent manner, either increasing 41 , 42 , 43 or decreasing, 44 depending on the cell/tissue type and radiation regimen. Increased CD206-expressing myeloid cells in more aggressive recurrent GBM samples compared to newly diagnosed cases supports previous findings, indicating the role of myeloid cells in GBM tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…31 Similarly, visualization of CD47 expression may help identify tumors amenable to macrophage based therapies. Both PD-L1 and CD47 inhibitors have been demonstrated to synergize with radiotherapy in preclinical models; [32][33][34][35] enhancing the effectiveness of radiotherapy with AGuIX could further increase the potency of this combination. Therefore, our primary focus was on developing AGuIX NPs that could effectively target and delineate crucial immunomarkers, specifically PD-L1 and CD47.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that ablative or hypofractionated radiation activates the antitumor CD8 + T-cell response more effectively than conventional fractionation schemes 35 38 . A single dose of 15 Gy radiation was compared to fractionated radiotherapy (5×3 Gy ) by Lugade et al 39 and it was found that in comparison to fractionated schemes, the 20 Gy single schedule elevated Antigen-Presenting Cell (APCs) and CD8 + T cell numbers and enhanced the bioactivity of CD8 + T cells.…”
Section: Introductionmentioning
confidence: 99%